Research Status of Artificial Intellegence in Education: A Systematic Literature Review (SLR) - Kayyis, Rahmatika (Universitas Pendidikan Ganesha, 2025)
The study on Artificial Intelligence (AI) in education highlights key findings that enhance understanding of the topic. It emphasizes the rapid growth of AI applications since 2015, focusing on intelligent tutoring systems, personalized learning environments, and administrative support. These applications show AI's potential to improve learning experiences and educational processes. Another significant finding is the rising importance of AI literacy and ethical considerations in education, with a shift in research towards addressing challenges related to preparing students for an AI-driven world. Keywords like